Influence of Fraud Hexagon on Fraudulent Financial Reports within State-Owned Companies Listed on the IDX in 2019-2023 - Jaiyanti, Jaiyanti; Safelia, Nela; Ridwan, Muhammad (PT. Riset Press International, 2024)
The phenomenon of financial statement fraud, which has a very large loss effect compared to other forms of fraud despite its low number of incidents, is the reason behind this study. Aside from that, there are still instances of financial statement fraud that call for additional investigation to determine how different independent variables—like financial stability, inadequate oversight, shifting directors or auditors, arrogance, and collusion—affect the dependent variable of financial statement fraud. The quantitative study makes use of secondary data from corporate annual reports. State-owned enterprises (BUMN) that were listed on the Indonesia Stock Exchange between 2019 and 2023 made up the study's population. Purposive sampling was used in the sampling process, resulting in 16 corporate samples over the course of five years and a total of 80 observation data points. Logistic regression analysis is the method of data analysis that is applied. The study's findings demonstrate that, in contrast to the factors of financial stability, change of auditor, change of directors, and arrogance, which have no effect on financial statement fraud, inefficient supervision and collaboration have a substantial impact.